WORK STRESS: A NEGATIVE CAUSE AND IMPACT ANALYSIS - Suparjiman, Suparjiman; Zulkarnaen, Wandy; Sasangka, Indra (2021)
This study aims to determine the causes of work stress, work stress levels, and the negative impact of work stress on employees at the Puskesmas. This research is a descriptive research with a qualitative approach. The results of this study indicate that the factors causing work stress that most often occur are the demands of tasks from superiors to complete the work, health problems, and uncertainty in technology, while the level of work stress that is felt is quite heavy and the impact of work stress is the most dominant. headaches, decreased productivity, and decreased levels of job satisfaction.